Pengaruh Ukuran Perusahaan, Utang, Profitabilitas Terhadap Praktik Income Smoothing Sebelum dan Saat Pandemi Covid-19 - Setiadi Alim Lim (Politeknik Ganesha Medan, 2022)
This study aims to determine whether there are differences in the income smoothing practice before and during the Covid-19 and to examine whether there is an effect of firm size, debt, and profitability on income smoothing practice before the Covid-19 (2017-2019), during the Covid-19 (2020-2021), and before and during the Covid-19 (2017-2021). The population of the study is all sub-industrial business entities providing health and pharmaceutical services on the IDX (Indonesian Stock Exchange). The sampling technique used was non-probability purposive sampling. The number of samples is 11 business entities. To test whether there are differences in income smoothing practice before and during the Covid-19, the Wilcoxon Signed Rank Test was used. Meanwhile, to examine the effect of firm size, debt, and profitability on income smoothing practice, binary logistic regression was used. The results of descriptive statistical analysis show that there is an increase in income smoothing practice during the Covid-19 compared to before the Covid-19. However, the results of the Wilcoxon Signed Rank Test show that there is no significant difference between the income smoothing practice before and during the Covid-19. The results of binary logistic regression show that firm size, debt, and profitability have no effect on income smoothing practice during the Covid-19 (2020-2021). While the period before the Covid-19 (2017-2019) and the period before and during the Covid-19 (2017-2021) firm size and profitability did not have a significant effect on income smoothing practice, but the debt had a significant effect on income smoothing practice.